Fundamental Frequency Coding in NofM Strategies for Cochlear Implants - Büchner, Andreas; Edler, Bernd; Nogueira, Waldo (118th AES Convention, 2005)
Current speech processing strategies for cochlear implants are based on decomposing the audio signals into multiple frequency bands, each one associated with one electrode. However, these bands are relatively wide to accurately encode tonal components of audio signals. To improve the encoding of tonal components and performance in cochlear implants, a new signal processing strategy has been developed. The technique is based on the principle of a so-called NofM strategy. These strategies stimulate fewer channels (N) per cycle than active electrodes (M) (NofM; N < M). However, the new strategy incorporates a fundamental frequency estimator which is used to emphasize the periodic structure of tonal components. The new technique was acutely tested on cochlear implant recipients. First intelligibility tests showed similar performance in speech perception between the new strategy and a standard NofM strategy.
UnivIS-Import:2015-04-20:Pub.2005.tech.IE.aulab.zentr.fundam